Surface finish and edge preparation of Al2O3 + MgO cutting inserts by grinding and their application in hard turning - Nardy, Maysa Freitas Mainardes; de Souza, Jose Vitor Candido [UNESP]; dos Santos, Sergio Francisco [UNESP]; de Sampaio Alves, Manoel Cleber [UNESP]; Ribeiro, Marcos Valerio [UNESP]; Antonialli, Armando Ítalo Sette; Ventura, Carlos Eiji Hirata (Springer Nature, 2024)
Due to their high hardness at elevated temperatures and chemical stability, alumina-based ceramic cutting tools have been successfully applied in the machining of ferrous materials, especially quenched and tempered steels. Their low fracture toughness, however, makes it difficult to finish them by grinding, as cracks and defects can occur. In addition, its application in machining processes demands appropriate edge preparation to avoid tool failure. Within this context, the paper aims to demonstrate the applicability of an experimental Al2O3 + MgO ceramic cutting insert in hard turning. For this, grinding tests were performed to determine the most appropriate conditions to improve its surface and edge quality. The effects of cutting and feed speeds, grinding wheel bonding material, and abrasive grain size were investigated. Moreover, different cutting-edge geometries were prepared in this tool material and tested in turning a hardened AISI 4140 steel (50 HRC) to determine their performance regarding tool life and workpiece roughness. The results demonstrated that a finer grinding wheel (D15) combined with high cutting (60 m/s) and feed (10 mm/min) speeds leads to the lowest surface roughness and edge chipping. In addition, both symmetric (Κ = 1) and asymmetric (Κ = 2) edge roundings led to higher tool lives in hard turning in comparison to a single chamfered tool, as they contributed to better load distribution in the cutting region. The paper provides information for the manufacture and application of alumina-based ceramic cutting inserts in the metalworking industry, as it disseminates good manufacturing practices and recommendations for appropriate cutting-edge geometry.
Keywords: Alumina; Ceramic; Hardened steel; Machining; Micro geometry